A review of vulvar carcinoma at Groote Schuur hospital for the period 2002 to 2012 with particular emphasis on HPV-related disease. Issue 1 (2nd January 2020) - Loggenberg, Francisca E; Adams, Tracey S
Abstract : Background: Vulvar carcinoma is rare and ranks fourth amongst the gynaecological malignancies. GLOBOCAN reported 44 235 new cases in 2018. There has been a rise in the number of cases of vulvar carcinoma in recent years and younger women are being affected by the disease. This rise is thought to be the result of more women being infected with human papilloma virus (HPV). HPV has been implicated in one of the pathways leading to the development of vulvar carcinoma. This study aims to review the cases of vulvar carcinoma at Groote Schuur Hospital and places particular emphasis on HPV-related disease. Methods: The study is a retrospective descriptive study of patients with vulvar carcinoma at Groote Schuur Hospital for the period 2002 to 2012. The study population included women with vulvar carcinoma who attended the multidisciplinary combined cancer clinic. Data were collected from folder reviews and an existing cancer database. Data were entered into data collection sheets that recorded patient demographics, disease aetiology, HIV status, treatment received, recurrences and multifocal disease. The analysis was performed using the R computing environment (RStudio Version 1.1.463) and MS Excel version 1808. Estimates of patient survival were computed using the Kaplan–Meier estimator. Results: There were 125 cases included in the study for the period 2002–2012. Data analysis revealed that 119 (95.2%) of the cases were squamous cell carcinomas. Among the squamous cell cancers, 98 (82.4%) had evidence of HPV disease, 18 (15.1%) occurred in patients with lichen sclerosus and 3 (2.5%) of patients had dual pathology. The mean age of the patients was 54.76 (SD 16.59) years. The youngest patient was 21 and the oldest 92 years of age. Of the 125 patients, 101 patients had clinical or histological evidence of HPV disease. In 76 patients (60.8%) the HIV status was known, of whom 75% were HIV negative and 25% HIV positive. Multifocal disease was present in 38.6% of the patients. Conclusion: This study revealed that there is a high burden of HPV-related disease at this centre, with younger women being affected by the disease. Patients are developing invasive disease despite their HIV status.